The Use of Micro Video to Support Student Engagement in Online Learning - Mawarni, Sella; Hartoto (Indonesian Journal of Learning Education and Counseling, 2025)
One of the challenges in online learning is the lack of student engagement in independent learning. The role of learning content significantly influences students' willingness to access and engage with the provided materials. This issue can be addressed through the use of microvideo learning content. Microvideos are short-duration video formats designed for efficient content delivery. This study aims to describe the use of microvideos in online learning and to analyze students' participation rates and learning completion. A qualitative descriptive research method was employed, involving 167 students enrolled in the Information and Communication Technology course. The findings reveal that student participation reached 90.42%, with a 100% learning completion rate. The use of microvideos in short-duration formats effectively reduces students' cognitive load.